Fortune Fishing Center / Husnulhadi Abd Nasir … [et al.] - Abd Nasir, Husnulhadi; Abd Rahim, Azran Fitri; Juminen, Noramin; Hasnan, Rosmadi; Azhan, Anies Suzana (2000)
Praise to Allah for giving us the strength and the patience to complete this business plan. Without strength, effort and patient this business will be useful for all of us. It also teach us to co-operate among us. First of all, I would like to express my gratitude and appreciation to our lecturer Puan Rahimah for her valuable suggestions guidance and constant encouragement. I am also grateful and indebted to my beloved members group for their support and teamwork to completed this business plan. Without their teamwork this project could not be done. This business plan gave us knowledge about entrepreneurship. We also hope this will be our first step in business world. Last but not least my special thanks to my family and friends for their encouragement and support throughout the preparation of this business plan. While much of the credit for the strength of this project paper is theirs, we are responsible for the weakness that remain.